Sunteți pe pagina 1din 22

1

Chapter 5
Examples

Functions

of functions:

1. f (x) = 3x 2, or y = x2 sin x, or z = x2 + y 2.
2. Given any country, assign to it its capital.
3. Given any student, assign to him/her the respective University number.

Definition (5.1.1)

Let A and B be nonempty sets. A function from A to B

(denoted by f : A B) is a relation (A, B, f ) satisfying the following conditions:

1. For each a A there exists b B such that (a, b) f , and


2. if (a, b) and (a, c) are both in f , then b = c.

The first condition says that for each a A, there is a b B which is related to
a. For instance, b = sin a has this property, but b = log a doesnt since for
a = 1, there is no such b.
The second condition says that the b B which is related to a is unambiguously
determined. Hence the relation that (a, b) f means a and b are brothers, is not a
function.
Since for each given a A, b is uniquely determined, we denote b by f (a).

See the example at the bottom of p.103.


Do Exercise 5.1.2, 5.1.3.
Refer to figure 5.1.
In definition 5.1.1, the set A is called the domain of f , denoted by Dom(f ), and
the the set B is called the codomain of f , denoted by Codom(f ). The set
{b B : there exists an a A such that b = f (a)}
is called the range or image of f , denoted by Ran(f ).
Theroem (5.1.7)

If f : A B and g : A B are two functions, then

f = g if and only if for each a A, f (a) = g(a).


Proof

We check that the two relations (A, B, f ) and (A, B, g) are equal, that

is, they have equal graphs f and g. According to the definition of functions
f = {(a, f (a)) : a A}, g = {(a, g(a)) : a A}.
Whence the conclusion of the theorem follows.
5.1.8
The inverse of a function is not necessarily a function. See figure 5.1.
Defintion (5.1.8)

A function f : A B is said to be one-to-one or injective if

given any b B, there is at most one a A for which b = f (a).


A function f : A B is said to be onto or surjective if for each b B, there is at
least one a A for which b = f (a). In other words, f is onto if Codom(f ) =
Ran(f ).
A function that is both one-to-one and onto is called a one-to-one
correspondence or bijective function.
Remark

To prove f is one-to-one, we let a, c be any elements in A such that

f (a) = f (c) and then proceed to show that a = c.


Examples

1. The function f : R+ R given by f (x) = x2 is one-to-one. But if the domain


is changed to R then the function is not one-to-one. (Why?) Is the function
surjective?
2. Let A be any nonempty set and let B be any set. The function g : P(A) P(B)
given by g(X) = X B is not injective nor surjective. Under what condition
will g be surjective? Injective?
Exercises 5.1.14
3. f (x) = x3 x is not one-to-one, since f (1) = 0 = f (0).
4. f (x) = ex is one-to-one: f (x) is an increasing function, so f (x) = ex = f (y) =

ey implies x = y.

5.2 Composition and Inverses


If f : A B and g : B C are functions, then the relation g f : A C is also
a function. Indeed, for any a A, there is a unique b B such that b = f (a), and
then there is a unique c C such that c = g(b) = g(f (a)) = (g f )(a).
(g f ) : A C is called the composition of f and g. For any a A,
(g f )(a) = g(f (a)).

Exercises (5.2.2)

1. f is surjective does not imply g f is surjective.


Example: A = B = C = {1, 2}.
f : A B given by f (1) = 1, f (2) = 2;
g : B C given by g(1) = g(2) = 1.
2. g is surjective does not imply g f is surjective.
Example: A = B = C = {1, 2}.
f : A B given by f (1) = f (2) = 1;
g : B C given by g(1) = 1, g(2) = 2.
3. f is one-to-one does not imply g f is one-to-one.

4. g is one-to-one does not imply g f is one-to-one.

Theorem (5.2.3)

Suppose that f : A B and g : B C are functions.

Then the following hold.


1. If f and g are both one-to-one, g f is one-to-one.
2. If f and g are both onto, g f is onto.

Proof

of 2. For any z C, there exists a certain y B such that z = g(y).

Since f is also onto, there exists an x A such that y = f (x). Hence,


z = g(y) = g(f (x)) = g f (x). So, g f is onto.

10

Problems (5.2.4)

1. If g f is one-to-one, then f must also be one-to-one.


Proof Let x, y A such that f (x) = f (y). Then g(f (x)) = g(f (y)). Hence,
g f (x) = g f (y). Since g f is injective, x = y, as desired.

2. g f one-to-one implies g one-to-one?

3. g f surjective implies f surjective?

4. g f surjective implies g surjective?

11

Theorem (5.2.5)

If f : A B, g : B C, h : C D are functions, then


h (g f ) = (h g) f.

In other words, the composition of functions is associative.


Proof

The functions on both sides have the same domain A and the same

codomain D. We, therefore, need only to show that, for each x A,


h (g f )(x) = (h g) f (x).

Theorem (5.2.7)

Let f : A B be a function. The relation (B, A, I), where


I = {(f (a), a) : a A},

12

is a function if and only if f is bijective. In such case, we write f 1 to denote


this function, which is called the inverse of f .
Proof

First we assume f is bijective and proceed to show that I is a function.

Since Ran(f ) = B, every element b B is of the form f (a) for some a A. So


(b, a) I. Furthermore, if c A such that (b, c) is also in I, then by the definition
of I, b = f (a) = f (c). Hence a = c. Thus, I is a function. In addition, we see
that, the function I is also bijective.
Conversely, assume that I is a function. Then every element in B is of the form
f (a) for some a A. Hence f is surjective. If a, c are elements in A such that
f (a) = f (c), then, by defintion, (f (a), a), (f (c), c) are both in I. But I is a
function, hence a = c. This shows that f is also injective.

13

Theorem (5.2.9)

Let f : A B be a function.

Part I. If f is a one-to-one correspondence, the following statements hold.


1. f f 1 = IB , the identity function on B, that is IB (b) = b for every b B.
2. f 1 f = IA, the identity function on A, that is IA(a) = a for every a A.
3. If g : B A is any function for which f g = IB or g f = IA, then g = f 1.
In other words, f 1 is the only function which satisfies the composition laws
in 1 or 2 above.
Part II. If there exists a function g : B A such that g f = IA and
f g = IB , then f is a one-to-one correspondence, and g = f 1, f = g 1.

14

Proof
Part I. We only prove 3. From f g = IB , we have
f 1 (f g) = f 1 IB = f 1.
The left hand side, by Theorem 5.2.5, is equal to (f 1 f ) g = IA g = g.
Similarly, g f = IA implies (g f ) f 1 = IA f 1, which then implies, on
invoking Theorem 5.2.5 again, that f 1 = g (f f 1) = g IB = g.
Part II. g f is injective implies f is injective. g f is surjective implies g is
surjective. Since identity functions are bijective, g f = IA implies f is injective,
and f g = IB implies f is surjective. Hence f is bijective. The desired conclusion

15

then follows from Part I 3.


Theorem (5.2.10)

If both h : A B and k : B C are bijective, then k h

is also a bijective function. Furthermore, (k h)1 = h1 k 1.


5.3

Images and Inverse Images

Definition (5.3.7)

Let f : A B be a function. For any subset T of A, the set

f (T ) = {b B : there is some t T with f (t) = b} = {f (t) : t T }


is called the image of T under the function f . Thus, Ran (f ) = f (A).
Example (5.3.10)

Let f : R R be given by f (x) = x2. Then

16

f ([2, 10]) = [0, 100].


f ({0, 1}) = {0, 1}.
f () = .

Note

In the notation f (T ), T is a subset of A and f (T ) is a subset of B.

Theorem (5.3.11)

Let f : A B be a function. For any subsets X, Y of A,

1. f (X Y ) = f (X) f (Y ),
2. f (X Y ) f (X) f (Y ),

17

3. f (X1) f (X) if X1 X.

Proof of 1. By 3, both f (X) and f (Y ) are subsets of f (X Y ), hence,


f (X) f (Y ) f (X Y ). Conversely, for any z f (X Y ), z = f (t) for some
t X Y . If t X, then z f (X). If t Y , then z f (Y ). In any case,
z f (X) f (Y ).
Exercise

Give an example to show that equality in 2 may not hold.

Definition (5.3.1)

Let f : A B be a function. For any subset S of B, the set


f 1(B) = {a A : f (a) S}

18

is called the inverse image of the set S under the function f .


Examples

1. f 1(B) = A.
2. Suppose f : R R is given by f (x) = x2. Then
f

([1, 2]) = [ 2, 1] [1, 2],

f 1({0}) = {0},

1
f ({3}) = { 3, 3},
f 1([1, 4]) = [2, 2],
f 1(R) = R.

19

Note

The inverse image f 1(S) is one single symbol. It is not the function f 1

on S, because, in general f is not bijective and its inverse is not a function.


Theorem (5.3.6)

Let f : A B be a function. For any subsets R and S of

B,
1. f 1(R S) = f 1(R) f 1(S),
2. f 1(R S) = f 1(R) f 1(S),
3. f 1(B\S) = A\f 1(S),
4. f 1(R1) f 1(R) if R1 R.

20

Proof

of 2. f 1(R) f 1(R S) and , f 1(S) f 1(R S). Therefore

f 1(R) f 1(S) f 1(R S).


Conversely, for any x f 1(R S), by definition of inverse image, f (x) R S.
Therefore, x R or x S. Hence, x f 1(R) or x f 1(S) . Consequently,
x f 1(R) f 1(S). This shows that f 1(R S) f 1(R) f 1(S).
Combining with the previous inclusion, we get that
f 1(R S) = f 1(R) f 1(S).
5.5

Sequences

Definition (5.5.1)
a sequence in A.

Let A be a nonempty set. Any function s : N A is called

21

Usual notation for a sequence in A is (ai) or more explicitly: a1, a1, a2, . . . , an, . . .,
where ai = s(i).
Examples

1. The harmonic sequence: 1, 12 , 13 , 14 , . . . .


2. The Fibonacci sequence: 1, 1, 2, 3, 5, 8, . . . .
3. The set A = R R and an = (2n + 1, sin( 41 n)).

Subsequence

22

Example

The sequence (ai) of squares: 1, 4, 9, 16, 25, 36, 49, . . . has the

subsequence 1, 9, 25, 49, . . . consisting of the odd squares. The terms of the
subsequence are a1, a3, a5, . . ..
Definition (5.5.18)

Let (ai) be a sequence in a set A. If (ni) is a strictly

increasing sequence in N (that is n1 < n2 < n3 < n4 < . . .), then the sequence
an1 , an2 , an3 , . . .
is a subsequence of (ai) and we denote this subsequence by (sni ).
Do Exercise 5.5.19.
Read Theorem 5.5.21 and Theorem 5.5.22.

S-ar putea să vă placă și